MEMAHAMI PERILAKU KONSUMEN MUSLIM SEBELUM DAN SELAMA MASA PANDEMI COVID-19 - Thithit Romadhona; Mirwan Surya Perdhana (Jurnal Ilmiah Ekonomi Islam, 2022)
Based on a preliminary study that the author conducted through direct interviews with people who act as financial regulators in a family regarding changes in purchasing during the covid-19 pandemic, it shows that perceptions and buying behavior vary. Further research on the impact of the COVID-19 pandemic on changes in consumer buying behavior towards attitude taking in deciding to buy an item or service. This needs to be done because Indonesia is a country that does not enforce a lockdown so that this condition will lead to different behavior from conditions that occur abroad. The purpose of this study is to analyze changes in consumer buying behavior in Indonesia towards the basic needs of goods and services during the covid-19 pandemic in Indonesia and the factors that play a role in determining consumer purchasing decisions in Indonesia for basic goods and services before and during the covid-19 pandemic. Samples were taken using purposive sampling technique with a total of 30 consumers. Data analysis using structural equation modeling. Based on the results of the study, changes in consumer buying behavior in Indonesia towards the basic needs of goods and services during the Covid-19 pandemic in Indonesia were in the shift from offline buying patterns to online, as well as a shift from purchasing products purchased during the Covid-19 pandemic which switched from Posts for traveling activities, shopping for clothing needs and tertiary needs switch to health products such as hand sanitizers, vitamins and masks, as well as data quotas that support work from home activities and learning activities for those who already have school-age children. Factors that play a role in determining the purchase decision are the convenience, competitive prices and quality of health products. Keywords: consumer behavior, pandemic, Covid-19., Muslim